EFEKTIVITAS PELAKSANAAN PROGRAM DESA MAJU INHIL JAYA (DMIJ) TERINTEGRASI DI DESA PANGLIMA RAJA KECAMATAN CONCONG KABUPATEN INDRAGIRI HILIR - Sri Anisha Medifiah; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The Integrated Desa Maju Inhil Jaya (DMIJ) Program is the flagship program of the Indragiri Hilir Regency Government. This study aims to determine the effectiveness of the implementation of the Integrated Desa Maju Inhil Jaya (DMIJ) program and the inhibiting factors for the implementation of the Integrated Desa Advanced Inhil Jaya (DMIJ) program in Panglima Raja Village, Concong Subdistrict, Indragiri Hilir Regency. The results showed that the implementation of the Integrated Village Forward Inhil Jaya (DMIJ) Village in Panglima Raja Village, Concong District, Indragiri Hilir Regency that covers 4 (four) areas of activity have not been carried out properly, in the field of village administration and in the field of village development it can be said to be effective, because of development. which was implemented in 2019 has been carried out. While the field of community development, and the field of empowerment of village communities cannot be said to be effective, because the impact of the activities in the field of empowerment of the Integrated Village Forward Inhil Jaya (DMIJ) program has not been fully felt by the community, the program's contribution is still minimal. The obstacles to the implementation of the integrated DMJ program in the Panglima Raja Village are; limited means of transportation, poor road conditions, low human resource capacity, limited costs. Keywords: Effectiveness, Integrated Maju Inhil Jaya Village Program